“SEHARI MENJADI SENIMAN” SEBAGAI IMPLEMENTASI WISATA EDUKASI SENI BUDAYA SIDOARJO - Mandarani, Vidya; Susilo, Joko; Akbar, Ali; Prapanca, Detak; Sari, Raras Hafiidha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This community service activity aims to introduce and foster appreciation for Sidoarjo's local arts and culture through a participatory educational tourism approach. The